Mild anxiety and depression related to elevated dopamine level - Fidianingsih, Ika; Nurmasitoh, Titis; Arjana, Adika Zhulhi; Devita, Ninda; Khoiriyah, Umatul (Faculty of Medicine, Trisakti University, 2019)
BackgroundDopamine is an important neurotransmitter that plays a role in the pathogenesis of anxiety and depression. Dopamine secretion occurs when there is a pleasurable stimulus. Blood dopamine levels have the potential to be developed as biomarkers of depression or anxiety, but previous studies related to the relationship between dopamine levels and levels of anxiety and depression are still controversial. The purpose of this study was to determine the correlation between anxiety and depression score with dopamine level in young adults. MethodsThis was an observational cross sectional study. A total of 43 subjects aged 18 to 40 years were recruited by consecutive non-random sampling according to inclusion and exclusion criteria. Anxiety and depression were assessed using the Beck anxiety inventory and Beck depression inventory-II questionnaire. Dopamine plasma level was measured using the enzyme-linked immunosorbent assay (ELISA). The Spearman rho correlation test was used to analyze the data and p<0.05 was considered significant.Results The median dopamine levels in respondents with mild, moderate and severe anxiety were respectively: 77.79; 63.43; 62.51 ng/mL (p=0.043). The median dopamine levels in respondents with reasonable depression, mood disorder, moderate and severe depression were respectively: 79.2; 61,32; 62,51; 60.24 (p=0.001). Correlation test results showed a weak correlation between dopamine and anxiety (r=- 0.310) and a moderate correlation for depression (r=-0.505).ConclusionMild anxiety and depression were associated with elevated dopamine level in young adults. Further studies are required to confirm the role of dopamine metabolism in anxiety and depression in young adults.